SISTEM KESELAMATAN KERJA PADA PROYEK NORMALISASI SUNGAI - Khalid Rijaluddin (Jurnal Teknologi Berkelanjutan, 2015)
The working of river normalization is a construction project which has tendency to have the work accidents because of the high frequencies of very modern working equipments. The accidents of work can be influenced by three main factors such they are human factor, equipments factor and environment factor. Some of the recently research showed that the most domain factor which caused the work accidents was human factor since the workers have less knowledge and awareness in how the importance the safety working is.Our government has released a rule about safety working especially for construction sector, which is made in the rules of Transmigration and Labor Ministry No. Per-01/Men/1980. One of the system in the management of safety and healthy working which has been developed and had been made into fix guidance is called OHSAS (Occupational Health and Safety assessment Series) 18000. The purposes of OHSAS is not far away different from the purposes of SMK3 Permenaker they are to protect and reduce the amount of working accident potencies. But in the other side the application of the system is still in a quite distance of satisfaction and so far from optimal action so that we can have many info about the rate of working accidents happening in a seemly high frequencies. Generally, the real condition of the implementation of safety work has been known and done but the persons and institutions who involved in this implementation can not do it totally or as well as possible because of some reasons.Therefore, it should be make safety work implementation strategy in the river normalization to do Permen PU No. 09/2008 of July 1 2008. The government and the supplier signature the policy of K3, signature the aggrement K3 with the partner of work, create PreRK3K and RK3K, to do technical guidance K3, to do the training to make some expert professional of K3 and also to prepare the operational monitoring guidance and evaluate K3 and prepare the guidance of K3 application.